Faculty of Mathematics and Nature at the University of Lithuania and its development - Klusienė, Virginija; Narkevičienė, Bronė; Puišo, Judita (Lietuvos matematikos rinkinys, 2018)
The origins of the Faculty of Mathematics and Natural Sciences in Kaunas are the early 1920, when the Lithuanian Higher Courses were established and included the Mathematical-Physical Department. On the 16th of February 1922, the University of Lithuania was created in Kaunas and the Faculty of Mathematics and Nature was founded as well. It acted up until autumn in 1940. All the time from the very beginning until the suspension, the Dean of the faculty was Professor Zigmas Žemaitis. Later on the 1st of September 1993, the Faculty of Fundamental Sciences was established on the basis of two departments – Kaunas University of Technology Department of Higher Mathematics (later re-named to Department of Applied Mathematics) and Department of General Mathematics and Physics. On the 1st of January, 2014 the faculty received its historical title – the Faculty of Mathematics and Natural Sciences and now is celebrating 25 years of activity.
Keywords: courses; university; institute; faculty; department; mathematics; physics; science; activity